FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBERDAYAAN ANGGOTA GABUNGAN KELOMPOK TANI PADA SEKOLAH LAPANG - Lesi Oktiwanti (Jurnal Ilmiah Visi, 2016)
The purpose of this research is to describe and analyze the effects of resource, knowledge and skill opportunity for the power of Gapoktan members as well as to describe and analyze the factors mostly influencing the power of Gapokan members. The research was conducted in Gapoktan Subur Murni, Cikalong Village, Cimaung Sub-district, Bandung District, in 2010 applying quantitative descriptive method. The data were collected by distributing questionnairer to 78 samples and analyzed using path analysis. The research result indicate resource, knowledge and skill, and opportunity possess positive and significant effects to power. The analysis result stated resource has effect of 0.258, knowledge and skill of 0.434 (the highest), and opportunity of 0.14. Over all the independent variables possess the effect of 0.732 to dependent variable. For further research, it is recommended to search the effect of ‘power within’ to empowerment.